Enzimas exógenas na digestibilidade de nutrientes da ração para juvenis de tambaqui Colossoma macropomum - Magri Filho, Silvio (2013)
This work was produced and determined the activity of an enzyme complex extracted from the fungus Aspergillus awamori and evaluated the apparent digestibility coefficients (CDAs) of crude protein, gross energy and dry matter ration reference tambaqui with 3 increasing levels of enzyme solution obtained from the fungus. The experiment was a completely randomized design with four treatments (100ml water solution without enzyme/kg of ration, 100 ml of enzyme/kg feed, 150 ml of enzyme/kg of ration and 200 mL of enzymatic solution/Kg ration) and three replications in time. It was installed on Aquaculture Research Laboratory in the Department of Animal Science LAPOA - PUC Goiás. A total of 96 tambaqui, Colossoma macropomum, with an average weight of 55.69 (± 2.55) g, distributed in twelve tanks of 100 liters, system in closed recirculating water containing 8 fish per experimental unit. Fish were fed every hour in the morning, at 8:00 h, 9:00 h, 10:00 h, 11:00 h and 12:00 h. Thirty minutes after the last meal the fish were transferred to units collect feces for up to 300 L. To determine digestibility was added will feed the chromic oxide-III marked as inert. The addition of the enzyme solution improved the digestibility of the ration, increasing the utilization of dry matter, crude protein and gross energy in the inclusion level of 0.05% (P <0.05%).